Heat transfer analysis of special reinforced NSC-columns under severe fire conditions - Sismanis, Panagiotis G. (International journal of materials research, 2010)
The 3-D heat conduction equation was numerically solved and the temperature distribution inside two special metallic frames, loaded with the proper number of reinforced bars, encased by normal strength concrete in the final columnar form, and subject to intense fire conditions, was computed by time. Typical temperature profiles were applied for the simulation of the cellulosic and hydrocarbon kinds of fire. Heat transfer by radiation and convection was included in the surrounding the column medium under fire, testing various convective heat-transfer coefficients. Computational results were analyzed until the critical time period in which the integrity and the mechanical strength of the column were reversible, considering fire abatement until that time.